In situ valence modification of Pd/NiO nano-catalysts in supercritical water towards toluene oxidation. Issue 7 (8th March 2018) - Meng, Qingjie; Liu, Jiajia; Weng, Xiaole; Sun, Pengfei; Darr, Jawwad A.; Wu, Zhongbiao
Abstract : Pd 0 is more active than PdO x in toluene oxidation owing to its capability of activating gaseous oxygen at low temperatures and returning to the original state even with excess O2 . Abstract : Noble metals, e.g. Pd, are often made into hybrid or composite catalysts (with less expensive materials) to oxidize industry-source emitted volatile organic compounds (VOCs) at low temperatures. In general, the loadings of these metals should be optimized to reduce costs whilst maintaining activity. There exists the possibility to obtain highly active catalysts with low loadings of noble metals by properly tuning the valence state of the metal(s). However, the relationship between the valence state and its effect on catalyst performance is still a matter of debate. In this article, we used supercritical water (sc-H2 O), in the presence of oxidizing or reducing gases, as a feasible reaction medium to synthesize Pd/NiO hybrid nano-catalysts and in situ modify the valence state of Pd. After subjecting the catalysts to a range of analytical techniques, including XRD, H2 -TPR, DRIFT, TPSR, etc., we unveiled that Pd 0 is more active than PdO x and metal oxides in the catalytic oxidation of toluene. This is mainly because the stabilized Pd 0 is capable of activating gaseous oxygen (and toluene) at low temperatures and returning to the original state by toluene even with excess oxygen. Although PdO x could desorb active oxygen under a reducing atmosphere and might assist in the oxygen spillover from NiO, it is difficult to convert into Pd 0 in an oxygen-rich environment. The developed Pd 0 -dominated catalyst was found to be robust and highly active after an ageing test with and without water vapour.